Chinese Notions of Public Space - Wenwen Sun (A+BE: Architecture and the Built Environment)
This thesis investigates the understanding and implementation of public space in the reformed Chinese context, particularly from the perspectives of urban design and architecture, by referring to the complex process and result of transculturation (transculturación). It delineates how public space as a Greco-Roman originated concept traversed the urban and architectural cultures of post-reform China, merging and negotiating with the local conditions, and evolved into a new phenomenon in Chinese urban design and architecture. By analysing public space as a cultural phenomenon, carrying specific meaning, through specific concepts and designs, this doctoral research develops an interpretative framework within which the meanings and transculturation of public space in Chinese urban design and architecture can be understood and elucidates potential for future urban design and architectural practices. Theoretically, it moves beyond the conventional research on public space that is primarily based on Western thoughts, an Indo-European notion, and a Greco-Roman tradition. Practically, it paves the way for future development of the design of public space, highlighting the cultural, social, and spatial dynamics in Chinese cities vis-à-vis the related political, economic, and governmental conditions within the context of ongoing globalisation.